Prevalence of Methicillin- Resistant Staphylococcus aureus and Antibacterial Susceptibility among Patients with Skin and Soft Tissue Infection at Ibb City, Yemen - Al-Khawlany, Rashad Saleh; Edrees, Wadhah Hassan; AL-Jaufy, Ahamed Yehia; Nasher, Mohammed AM; Al-Shehari, Wadee Abdullah; Reem, Alariqi; Almezgagi, Maged Mohammed (PSM Microbiology, 2021)
The increase of methicillin-resistant Staphylococcus aureus among patients is receiving more attention to health care. The present study aimed to evaluate the prevalence of Methicillin-resistant S.aureus (MRSA) between patients with infected skin and soft tissue at Ibb city, Yemen, and determine their antibacterial susceptibility profiles. A total of 189 patients were enrolled in this study between October 2007 and September 2008 at Al-Thawrah Hospital. Two specimens of each patient (1 of the nose and 1 of the infected site) were collected by sterile swabs and the MRSA was isolated and identified by standard bacteriological methods. The antibacterial susceptibility profiles were performed for the isolated MRSA. The overall prevalence rate of MRSA infection was 9.3% isolated from the nose and infected sites. The prevalence of isolated MRSA from the nose among males (45.2%) was higher than in females (4.8%). While a similar prevalence of MRSA among males and females with infected sites was found. The high prevalence of MRSA was among the age group of 18 to 29 years. Most MRSA isolates were isolated from the abscesses, ulcers, wound infection, and post-operation wounds. All isolates of MRSA were sensitive to vancomycin and completely resistant to oxacillin. The low rate prevalence of MRSA isolates in this work is considered the precursor for serious health problems. So, avoiding the empirical use of antibiotics and introducing effective guidelines for using antibiotics is required to control MRSA transmission in the hospital. The results of antimicrobial susceptibility testing should be combined with clinical information and experience when selecting the most appropriate antibiotic.